Norms and Construct Validity of the Rosenberg Self-Esteem Scale in Canadian High School Populations: Implications for Counselling - Bagley, Christopher; Bolitho, Floyd; Bertrand, Lorne (Canadian Journal of Counselling and Psychotherapy, 2007)
A random sample of Alberta high schools yielded data for 1,084 males and 1,024 females. Measures completed included the Rosenberg Self-Esteem Scale. Within each age and sex group a strong, unrotated factor was invariant. There was significant variation of mean scores across age-groups within female students. In each age group females had significantly lower self-esteem than males. Evidence of construct validity is derived from correlations with behavior problem categories; the McMaster measure of family relationships; and self-completion measures of school climate, and physical and sexual victimization in school. Possible uses for self-esteem measures in school counselling are proposed.